PENERAPAN TEKNIK KAIZEN BERBANTUAN ARENA NUMBERS GAME UNTUK MENINGKATKAN KEMAMPUAN NUMERASI SISWA SD NEGERI BANJARHARJO - Yusni Usman Ningrum (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
Based on the 2021 education report card, the numeracy ability of students at SD Negeri Banjarharjo requires intervention. The application of kaizen-assisted game techniques is an action to solve the problem. It is based on the theory that regular and continuous habituation can foster internal motivation to like that habituation, including playing with numbers and numeracy. This research explores how the application of kaizen techniques assisted by arena numbers games at SD Negeri Banjarharjo and its impact on improving students' numeracy skills. The respondents in this study were 121 students in grades 1-6 of SD Negeri Banjarharjo. This research is qualitative descriptive research that uses observation, interviews, and study documents as data collection instruments. The data obtained were analyzed using data triangulation techniques. The results showed that the kaizen technique assisted by arena numbers games has been implemented well and is able to increase student motivation in processing numbers and can improve students' numeracy skills.